2022
DOI: 10.1002/aur.2842
|View full text |Cite
|
Sign up to set email alerts
|

The importance of low IQ to early diagnosis of autism

Abstract: Some individuals can flexibly adapt to life's changing demands while others, in particular those with Autism Spectrum Disorder (ASD), find it challenging. The origin of early individual differences in cognitive abilities, the putative tools with which to navigate novel information in life, including in infants later diagnosed with ASD remains unexplored. Moreover, the role of intelligence quotient (IQ) vis-à-vis core features of autism remains debated. We systematically investigate the contribution of early IQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Regarding PIQ development, the results from the autistic group were heterogeneous, since PIQ significantly deteriorated for 16 children (Cluster 2), while mildly improving for 23 children (Clusters 1 and 3). The observed PIQ drop in Cluster 2 seems to be in line with Denisova and Lin's (2023) large‐scale longitudinal study that found an extremely rapid decline in PIQ in 10‐ to 70‐month‐old autistic children relative to TD children. The fact that the current study found either a decline or a mild rise in PIQ scores across the three clusters longitudinally, but no signs of considerable improvement—at least not of the size of the improvement that autistic children in Cluster 1 exhibited in their VIQ scores, implies that the developmental progress in autistic children's visuospatial abilities was rather limited.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding PIQ development, the results from the autistic group were heterogeneous, since PIQ significantly deteriorated for 16 children (Cluster 2), while mildly improving for 23 children (Clusters 1 and 3). The observed PIQ drop in Cluster 2 seems to be in line with Denisova and Lin's (2023) large‐scale longitudinal study that found an extremely rapid decline in PIQ in 10‐ to 70‐month‐old autistic children relative to TD children. The fact that the current study found either a decline or a mild rise in PIQ scores across the three clusters longitudinally, but no signs of considerable improvement—at least not of the size of the improvement that autistic children in Cluster 1 exhibited in their VIQ scores, implies that the developmental progress in autistic children's visuospatial abilities was rather limited.…”
Section: Discussionsupporting
confidence: 88%
“…Although not a core symptom in autism, intellectual functioning atypicalities are observed in autism since infancy (Bryson et al, 2007;Denisova & Lin, 2023). The existing literature on IQ measurements shows that autistic children tend to demonstrate a discrepancy between verbal and nonverbal intellectual abilities, indicating an atypical pattern of verbal and performance IQ differences (Ankenman et al, 2014;Black et al, 2009;Giofrè et al, 2019;Mayes & Calhoun, 2008;Nader et al, 2015Nader et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low cognitive ability is a major feature of ASD and is associated with greater autistic impairments ( 44 ). We find that intolerant deletions and duplications follow this pattern, such that they decrease cognitive ability and increase ASD risk.…”
Section: Discussionmentioning
confidence: 99%
“…This perspective considers complexities in the relationship between IQ and autism diagnosis within a novel maturational framework (Figure 1). First, we clarify the neurobiological and genetic evidence that may explain the co-occurrence between ASD and Intellectual Disability (ID) (Maenner et al, 2023;Shaw et al, 2023) and lower IQs (Denisova & Lin, 2022), including the possibility that high IQ may "rescue" the social communication impairments. Second, we consider the important role of critical periods during growth and development, how impairment of transient processes during these critical developmental windows may interact with ASD risk genes, and how these, taken together, may contribute to some early-diagnosed ASD cases that also have lower IQ very early in infancy.…”
Section: Introductionmentioning
confidence: 99%